Arqueología urbana en el área central de la ciudad de Córdoba, Argentina : excavaciones en la sede Corporativa del Banco de la Provincia de Córdoba (2014-2016) - Izeta, Andrés D. (Access archaeology., 2017)
This work is part of a line of action proposed by the Institute of Anthropology of Córdoba (IDACOR), doubly dependent executing unit of the National Council of Scientific and Technical Research (CONICET) and the National University of Cordoba (UNC). This action requires the intervention of professional archaeologists in order to evaluate the impact produced by subsurface excavation in cases related to the development of real estate projects.